THE VARIOUS ROLES OF HEAT SHOCK PROTEINS IN PARKINSON DISEASE - Al Khatib, Ahed J; Laiche, Fatima; Al Asseiri, Mohammed; Qasem, A’aesha M; Al-Agedi, Hassan Shabi (European Scientific Journal, ESJ, 2013)
The present review study was conducted to bring the attention to various roles played by heat shock proteins (HSPs) in Parkinson Disease (PD). HSPs as chaperons play significant roles through offering cellular protection against multi- sources of stress. It has been suggested that HSPs could have a great potential to be involved as molecules for potential therapies in various diseases among which is PD. Because HSPs are involved almost in all cells, and because PD involves defects in brain and skeletal muscles, any improvement in cellular response through the reactivity of HSPs should be considered significant. We have also discussed the roles of various proteins included in HSPs, since they are varying according to their molecular weight with varying functions. We also aimed to bring more excitement to encourage researchers for conducting more studies in HSPs as targeted therapies in more details related to various proteins within the family of HSPs.